Analysis of operational risk management implementation at micro, small medium entreprises - Patricia Angelina; Caroline Angelina; Selli Selli; Stella Stella; Elza Theofhilia (Institute of Computer Science (IOCS), 2023)
The maximization of profits and the assumption of risk are inseparable elements of corporate management. The seafood restaurant industry offers promising future potential. Rezeki Seafood is one of the seafood restaurants in Batam City. This study aims to determine how Rezeki Seafood applies risk management, specifically in terms of strategic risk, operational risk, compliance risk, and tactical risk. This study approach is qualitative, and the acquired data will be examined. Observations and interviews were used to collect existing data. According to the findings of the investigation, Rezeki Seafood has a high amount of reputation-affecting operational risk, compliance risk, and strategic risk. Regarding risk, Rezeki Seafood demonstrates a high impact with a low chance. The conclusion of the research is that Rezeki Seafood restaurant has a high level of risk, especially in operational risk, compliance risk, and strategy risk. Risks related to reputation are one of the risks that often occur at Rezeki Seafood, where the factors that cause it come from the ability to overcome small problems quickly, employee problems, raw material problems, responsiveness to customer problems, and so on.